The Charm and Significance of Painting in the Modern World - He, Jie (International Journal of Computer Science and Information Technology, 2025)
This paper delves deep into the charm and significance of painting in the modern world. As an ancient art form, painting has witnessed numerous masterpieces throughout history, ranging from prehistoric cave paintings to classic works in the East and West. In modern society, it plays multiple important roles. As a medium for self - expression, artists such as Vincent van Gogh, Frida Kahlo, and Banksy convey their inner worlds and social views through painting. Painting can shape cultural identities, reflecting the values and histories of different cultures and contributing to the preservation of cultural heritage. Its therapeutic potential has been recognized in the field of psychology. Art therapy centered around painting can promote emotional expression, self - exploration, and healing, benefiting people of all ages and backgrounds. Technology has had a significant impact on painting. Digital tools have changed the way of creation, bringing both limitations and new possibilities. Meanwhile, technologies such as virtual exhibitions and digital restoration have revolutionized the methods of display and preservation. In the future, painting is expected to witness various style trends, such as the integration of art forms, the revival of traditional techniques, and the use of non - traditional materials. It will also adapt to social and environmental changes in terms of material selection and theme expression. In conclusion, painting, as the cornerstone of human expression, culture, and well - being, has an immortal legacy and will continue to be a source of inspiration and cultural richness.